A Wideband Reflector-Backed Antenna for Applications in GPR. (8th November 2021) - Raza, A.; Lin, W.; Ishfaq, M. K.; Inam, M.; Masud, F.; Dahri, M. H.
Abstract : A resistively loaded wideband slotted patch antenna with optimized performance on lower frequencies is proposed for ground-penetrating radar (GPR) applications. The proposed design is backed by an optimized reflector composed of a periodic array of square loop elements, which enhances the antenna's gain and directivity. The antenna shows good radiation characteristics and ease of integration with the GPR systems. The proposed structure features a compact size and wide bandwidth covering from 0.6 to 4.6 GHz. The peak gain of 7 dBi is achieved. The fabricated prototype of the antenna along with an integrated optimized reflective surface has overall dimensions of 18 × 22 × 5 cm 3 . The measured results validate the antenna's performance in both free space and sandy medium, which enlighten its use for GPR applications.